Comparison of Electrically Evoked Whole-Nerve Action Potential and Electrically Evoked Auditory Brainstem Response Thresholds in Nucleus CI24R Cochlear Implant Recipients - Hay-McCutcheon, Marcia J.; Brown, Carolyn J.; Clay, Kelly Schmidt; Seyle, Keely (Journal of the American Academy of Audiology, 2002)
In this study, differences between electrically evoked whole-nerve action potential (EAP) and electrically evoked auditory brainstem response (EABR) measurements within Nucleus CI24R cochlear implant recipients were evaluated. Precurved modiolus-hugging internal electrode arrays, such as the CI24R, are designed to provide more direct stimulation of neural elements of the modiolus. If the electrode array is closer to the modiolus, electrically evoked and behavioral levels might be lower than were previously recorded for the straight electrode array, the CI24M. EAP and EABR growth functions and behavioral levels were obtained for 10 postlingually deafened adults. Results revealed no significant differences between EAP and EABR threshold levels, and these levels were not significantly lower than those obtained using the CI24M.
Keywords: Cochlear implants; electrical action potential; electrical auditory brainstem response; electrically evoked auditory potentials; neural response telemetry